VLSI Design and Test for Systems Dependability - Asai, Shojiro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2019)
This book discusses the new roles that the VLSI (very-large-scale integration of semiconductor circuits) is taking for the safe, secure, and dependable design and operation of electronic systems. The book consists of three parts. Part I, as a general introduction to this vital topic, describes how electronic systems are designed and tested with particular emphasis on dependability engineering, where the simultaneous assessment of the detrimental outcome of failures and cost of their containment is made. This section also describes the related research project "Dependable VLSI Systems," in which the editor and authors of the book were involved for 8 years. Part II addresses various threats to the dependability of VLSIs as key systems components, including time-dependent degradations, variations in device characteristics, ionizing radiation, electromagnetic interference, design errors, and tampering, with discussion of technologies to counter those threats. Part III elaborates on the design and test technologies for dependability in such applications as control of robots and vehicles, data processing, and storage in a cloud environment and heterogeneous wireless telecommunications. This book is intended to be used as a reference for engineers who work on the design and testing of VLSI systems with particular attention to dependability. It can be used as a textbook in graduate courses as well. Readers interested in dependable systems from social and industrial-economic perspectives will also benefit from the discussions in this book.
Challenges and Opportunities in VLSI for Systems Dependability -- Design and Development of Electronic Systems for Quality and Dependability -- Radiation-Induced Soft Errors -- Electromagnetic Noises -- Variations in Device Characteristics -- Time-Dependent Degradation in Device Characteristics -- Connectivity in Wireless Telecommunications -- Connectivity in Electronic Packaging -- Responsiveness for Hard Real Time Control -- The Role of Security LSI and the Example of Malicious Attacks -- Verification and Test Coverage -- Unknown Threats and Provisions -- Design Automation for Reliability -- Formal Verification and Debugging of VLSI Logic Design for Systems Dependability:Experiments and Evaluation -- Virtualization: System-Level Fault Simulation of SRAM Errors in  Automotive Electronic Control Systems -- DART - A Concept of In-Field Testing for Enhancing System De-pendability -- Design of SRAM Resilient against Dynamic Voltage Variations -- Design and Applications of Dependable Non-Volatile Memory Systems -- Network-on-Chip Based Multiple-Core Centrized ECUs for Safety-Critical Automotive Applications -- An On-Chip Router Architecture for Dependable Multicore Processor -- Wireless Interconnect in Electronic Systems -- Wireless Power Delivery Resilient against Loading Variations -- Extended Dependable Air: Use of Satellites in Boosting Dependability of PublicWireless Communications -- Responsive Multithreaded Processor for Hard Real-Time Robotic Applications -- A Low-Latency DMR Architecture with Fast Checkpoint Recovery Scheme Using  Simultaneously Copyable SRAM -- A 3D-VLSI Architecture for Future Automotive Visual Recognition -- Applications of Reconfigurable Processors as Embedded Automatons in the IoT Sensor Networks in Space -- An FPGA Implementation of Comprehensive Security Functions for Systems-Level Authentication -- SRAM-Based Physically Unclonable Functions (PUFs) to Generate Signature out of Silicon for Authentication and Encryption.
Keywords: Electronic circuits; Security systems; Engineering design; Data protection; Electronic Circuits and Systems; Security Science and Technology; Engineering Design; Data and Information Security